Peran PERAN MEDIA SOSIAL INSTAGRAM @UMAH_GRINGSING_TENGANAN DALAM MEMPERTAHANKAN EKSISTENSI DESA WISATA TENGANAN: THE ROLE OF INSTAGRAM SOCIAL MEDIA @UMAH_GRINGSING_TENGANAN IN MAINTAINING THE EXISTENCE OF TENGANAN TOURISM VILLAGE - Putu Sri Handayani; Krisna Naraiswari, Ayu Nanda; Dian Sasmitha Diarta, Ni Luh Gede (Bogor Hospitality Journal, 2024)
This research aims to explore the effectiveness of the Instagram account @umah_gringsing_tenganan in promoting the Tenganan Tourism Village, with a focus on the marketing communication strategies used and their impact on increasing tourist visits. The background to this research is the increasing competition in the tourism sector, especially in the digital era, where social media has become an important tool for introducing culture and tourist destinations. The method used is a descriptive qualitative approach, with data collection through in-depth interviews with Instagram account managers and analysis of uploaded content. The research results show that the @umah_gringsing_tenganan account has strengths in attractive visualization and in-depth cultural storytelling, which successfully builds an emotional connection with the audience. However, the weakness lies in the quality of the content due to limited resources and experience of the management team. Opportunities include cultural tourism trends and potential collaborations with influencers, while threats faced include competition with other destinations and the spread of misinformation. The conclusion of this research confirms that an effective marketing communication strategy through social media can increase the visibility and attractiveness of the Tenganan Tourism Village, as well as make a significant contribution to tourist visits. Therefore, it is recommended that account managers continue to develop interesting content and consider collaborating with other parties to increase village exposure.